Latin American Theoretical Approaches to Development - Lechini, Gladys Teresita (2021)
Latin American (LA) theoretical approaches have not always been recognised as such by mainstream International Relations scholars and even in the LA region itself. Some do not admit LA theories as a School of Thought, arguing that “it would be absurd to build a theory of international relations based in countries such as Malaysia and Costa Rica” (Waltz, 1979, p. 72 in Frasson-Quenoz, 2016). This statement supports the thinking that a general theory of international politics must necessarily be based on the great powers (Tickner et al., 2012).Our objective here is to briefly explain the evolution of LA School of Thought on Development from the 1950s until the present day.